2020
DOI: 10.1002/brb3.1715
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative ketamine for reduction in postpartum depressive symptoms after cesarean delivery: A double‐blind, randomized clinical trial

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 47 publications
1
37
0
Order By: Relevance
“…After screening the titles and abstracts, only thirty studies were considered eligible for full reading. Twelve studies met all the selection criteria [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] as determined through browsing the titles, abstracts, and full texts ( Figure 1 ). The included articles were published between 2005 and 2020, with sample sizes ranging from 28 to 163.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…After screening the titles and abstracts, only thirty studies were considered eligible for full reading. Twelve studies met all the selection criteria [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ] as determined through browsing the titles, abstracts, and full texts ( Figure 1 ). The included articles were published between 2005 and 2020, with sample sizes ranging from 28 to 163.…”
Section: Resultsmentioning
confidence: 99%
“…And in this study, a significant difference was found in the incidence of headaches between the ketamine and control groups in the immediate postoperative period and 4 h postoperatively, while no significant difference was found in the 12-h and 24-h postoperative periods. However, in another study [ 18 ], who recorded the incidence of headaches at 5 min postoperatively, 15 min postoperatively, and at the time of leaving the operating room, the incidence of headaches was higher in the ketamine group than in the control group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some clinical studies that report effective prevention of postpartum depression in women undergoing cesarean section with prophylactic ketamine ( Ma et al, 2019 ; Yao et al, 2020 ), but additional multicenter double blind crossover studies are required to confirm this. There is also an ongoing clinical trial (NCT03927378) investigating S-ketamine for PPD, no results have been published to date.…”
Section: Introductionmentioning
confidence: 99%
“…It has a wide therapeutic range and is safely used as an anesthetic for patients in all age groups and for a variety surgical procedures [11,12]. In addition, recent research on ketamine as prophylaxis for postpartum depression [13,14] has created interest in the question of ketamine excretion in breastmilk, and a pharmacodynamic study in breastfeeding women is underway (ClinicalTrials.gov identifier: NCT04285684).…”
Section: Introductionmentioning
confidence: 99%